Reforming and Rebuilding Lebanon’s Port Sector Part II : Policies and Solutions for Digitalizing the Port of Beirut - World Bank (World Bank, Washington, DC, 2021)
The resilience of the Lebanese port sector has proven to be low. The impact of the ongoing economic crisis, the COVID-19 pandemic, and the Port of Beirut (PoB) explosion has traumatized the sector and exposed its weaknesses and inabilities to predict, identify, and respond to external risks. Anticipated slow recovery is expected to intensify the burden on the economy while opportunity costs are high given the recent port developments in the Eastern Mediterranean region and globally. Digitalization is one of key foundational stones for reconstruction. The “Reforming and RebuildingLebanon’s Port Sector “ note that the World Bank published in January 2020 highlights that there is a unique opportunity for rebuilding better the PoB and recommends a roadmap around four key building blocks: i) a new governance structure based on the landlord port model; ii) efficient and modern trade compliance procedures; iii) open and transparent bidding processes for selecting investors, operators, or concessionaires; and iv) quality infrastructure contingent on a national port strategy and a revised PoB masterplan.